Pengaruh Ketidakpastian Lingkungan terhadap Audit Report Lag dengan Corporate Governance sebagai Variabel Moderasi: (Studi Empiris pada Perusahaan Sektor Consumer Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023) (Jurnal Kendali Akuntansi, 2025)
Timeliness of financial reporting is crucial for maintaining company transparency and credibility, especially in uncertain environmental conditions. This study attempts to evaluate the impact of environmental uncertainty on audit report lag, moderated by corporate governance mechanisms (through the proportion of independent commissioners, audit committee size, and audit quality). This study applies a quantitative methodology, utilizing data from 106 companies in the consumer cyclicals sector from 2020–2023, and analyzed using multiple linear regression. The findings of the study demonstrate that environmental uncertainty has positive significant effect on audit report lag. Audit committee size was found to weaken this relationship, while the percentage of commissioners who are independent and audit quality did not act as moderators. The ineffectiveness of independent commissioners is attributed to their limited direct influence on reporting policies, whereas Big Four auditors tend to prioritize prudence, thereby extending the audit process. These findings have implications for companies to enhance the effectiveness of internal oversight in responding to external dynamics to minimize audit report lag.